Prognosis and treatment strategies for atrial fibrillation in heart failure with mildly reduced ejection fraction - Schupp, Tobias; Schmitt, Alexander; Reinhardt, Marielen; Abel, Noah; Lau, Felix; Abumayyaleh, Mohammad S. A.; Dudda, Jonas; Weidner, Kathrin; Ayoub, Mohamed; Akın, Muharrem; Müller, Julian; Akın, Ibrahim; et al. (European journal of preventive cardiology, 2024)
By now, limited data regarding the prognostic impact of comorbidities in heart failure with mildly reduced ejection fraction (HFmrEF) are available, contributing to the overall limited evidence regarding the treatment of patients with HFmrEF. The present study investigates the prognostic impact of the presence of atrial fibrillation (AF) on the long-term prognosis of patients with HFmrEF using a large retrospective study of 2148 patients hospitalized with HFmrEF from 2016 to 2022. Atrial fibrillation was prevalent in 43% of patients with HFmrEF and independently associated with an increased risk of the composite of long-term all-cause mortality and heart failure-related rehospitalization. Adverse prognosis in patients with concomitant AF was confirmed using multivariable Cox regression analyses and propensity score matching. Finally, the achievement of rhythm control may be associated with a lower risk of long-term all-cause mortality. Further studies are needed to demonstrate the effect of rhythm control and catheter ablation for AF in patients with HFmrEF.The study investigates the prognosis of atrial fibrillation (AF) in patients with heart failure with mildly reduced ejection fraction (HFmrEF). Data concerning the prognostic impact of AF in patients with HFmrEF is scarce.Consecutive patients with HFmrEF [i.e. left ventricular ejection fraction 41-49% and signs and/or symptoms of heart failure (HF)] were retrospectively included at one institution from 2016 to 2022. Patients with AF were compared with patients without with regard to the primary composite endpoint of all-cause mortality and HF-related rehospitalization at 30 months (median follow-up). Statistical analyses included Kaplan-Meier, multivariable Cox proportional regression analyses, and propensity score matching. A total of 2148 patients with HFmrEF were included with an overall prevalence of AF of 43%. The presence of AF was associated with a higher risk of the primary composite endpoint all-cause mortality and HF-related rehospitalization at 30 months [hazard ratio (HR) = 2.068; 95% confidence interval (CI) 1.802-2.375; P = 0.01], which was confirmed after propensity score matching (HR = 1.494; 95% CI 1.216-1.835; P = 0.01). AF was an independent predictor of both all-cause mortality (HR = 1.340; 95% CI 1.066-1.685; P = 0.01) and HF-related rehospitalization (HR = 2.061; 95% CI 1.538-2.696; P = 0.01). Finally, rhythm control may be associated with lower risk of all-cause mortality compared with rate control for AF (HR = 0.342; 95% CI 0.199-0.587; P = 0.01).Atrial fibrillation affects 43% of patients with HFmrEF and represents an independent predictor of adverse long-term prognosis.
Veröffentlicht: 3. Juni 2024
Gesehen am 26.11.2024